Voting and transfer payments in a threshold public goods game - Christian Feige; Karl-Martin Ehrhart (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2015)
In a laboratory experiment, we investigate if groups consisting of two heterogeneous player types (with different marginal contribution costs) can increase their total contributions and payoffs in a threshold public goods game if transfer payments are possible among the players. We find that transfer payments are indeed used in many groups to shift contributions from high-cost players to low-cost players, thereby not only increasing social welfare, but also equalizing payoffs. In a repeated setting with individual voluntary contributions and transfers, this redistribution effect takes a few rounds to manifest and high-cost players benefit the most in terms of payoffs. The same beneficial effect of transfer payments can also be achieved in a one-shot setting by having the groups vote unanimously on contributions and transfers of all players.
urn:nbn:de:swb:90-504425
Keywords: C92; D71; H41; 330; threshold public good; transfer payments; experimental economics; unanimous voting; committee; heterogeneity